THE EFFECT OF DIGITAL MEDIA ON JOB PERFORMANCE: A CASE STUDY OF TELECOMMUNICATION EMPLOYEES IN IHS TOWERS AND ZTE NIGERIA LIMITED - Nwankwo , Chinedu Okwudili (Research Journal of Literature, Languages and Linguistics, 2024)
This study examined digital media and job performance of telecommunication employees of IHS Tower and ZTE Nigeria Limited in Lagos State, Nigeria. The objectives of the study were to find out the digital media tools that help telecommunication employees of IHS Tower and ZTE Nigeria Limited in their in job performance. The theoretical framework of the study was the adaptive structural theory and system theory. The research design adopted for this study was the descriptive survey design. The population of this study consisted of the IHS Tower and ZTE Nigeria Limited workers (staff) in Lagos state. According to the telecommunication companies Administrative Officers in 2023, the total population of IHS Tower is 600 and ZTE Nigeria Limited is 185. The total population is 785 (Seven hundred and eighty five). To obtain the required sample size, Krejcie and Morgan Table was used to obtain the sample size of 254. The sampling method adopted was multi-stage sampling and data for this study obtained using copies of questionnaire. Data were analysed using the descriptive and inferential statistical analysis. Finding revealed that the digital media tools telecommunication employees of IHS Tower and ZTE Nigeria Limited engage in job performance were Google drive, browsers, servers, media hub, YouTube, Websites, portal sites, podcasts, blogs, webcast, Skype, dropbox, Evernote, HBO Go, Textplus, Picassa, Androi and Flipboard. The study concluded that digital media tools employed by telecommunication employees for job performance, ranged from collaborative platforms like Goggle Drive and servers to communication tools such as chatbots and file sharing platforms. Based on the finding, the study recommended that organizations should employ digital media tools such as Goggle drive, browsers, servers, media hubs, YouTube, websites, cloud storage, file sharing platforms, assistant gadgets, for improved job performance.